Juxtaposing the Primary School Assessment Concepts and Practices in Singapore and Malaysia - Mohamed, Mazidah; Sallehhudin Abd Aziz, Mohd (International Journal of Engineering and Technology, 2018)
The assessment practices in schools have moved from the traditional way of assessing students, which is too exam oriented and relies heavily on standardized exams, towards a more holistic assessment which involves the integration of Central Assessment and School-based Assessment. This paper aims to review the relevant studies on Central Assessment, School-Based Assessment, Formative Assessment (FA) and Assessment for Learning (AfL) in Singapore and Malaysia. It begins with a brief history of assessment in Malaysia and Singapore. Then, it critically reviews the concepts of Formative Assessment and Assessment for Learning as practiced in both countries. From the review, some differences and challenges between the two educational systems particularly with regard to the implementation of classroom assessment are identified. These differences include the medium of instruction, the assessment system and the average class size. Despite the challenges, School-based Assessment, Formative Assessment and Assessment for Learning should be duly implemented regardless of the increased workload and the level of the teachersâ€™ skills in assessment. It is found that these factors do not adversely affect the practices of Formative Assessment and Assessment for Learning by the teachers.Â Â